The limits on the use of force in international dispute resolution the case of Somalia - Abdellaoui, Jamila El (Department of Private Law, 2026)
Somalia is often the first country that comes to mind when one searches for an example of a 'failed state.'1 The country has known civil strife for more than 15 years.2 After almost a decade of civil war, in which no functioning government existed, a peace process was initiated in early 2000.3 A Transitional National Government (TNG) was established in August 2000 but the newly acquired peace in the country soon proved to be short-lived.4 Another peace process followed in 2004, which finally led to the establishment of the Transitional Federal Government (TFG).5 Unfortunately, this regionally initiated peace process also failed to be inclusive and responsive to the root causes of the conflict that has ravaged the country for so long and fighting between different parties continued.